Expression of bacterial genes in plant cells. - Fraley, R T (1983)
Chimeric bacterial genes conferring resistance to aminoglycoside antibiotics have been inserted into the Agrobacterium tumefaciens tumor-inducing (Ti) plasmid and introduced into plant cells by in vitro transformation techniques. The chimeric genes contain the nopaline synthase 5' and 3' regulatory regions joined to the genes for neomycin phosphotransferase type I or type II. The chimeric genes were cloned into an intermediate vector, pMON120, and inserted into pTiB6S3 by recombination and then introduced into petunia and tobacco cells by cocultivating A. tumefaciens cells with protoplast-derived cells. Southern hybridization was used to confirm the presence of the chimeric genes in the transformed plant tissues. Expression of the chimeric genes was determined by the ability of the transformed cells to proliferate on medium containing normally inhibitory levels of kanamycin (50 micrograms/ml) or other aminoglycoside antibiotics. Plant cells transformed by wild-type pTiB6S3 or derivatives carrying the bacterial neomycin phosphotransferase genes with their own promoters failed to grow under these conditions. The significance of these results for plant genetic engineering is discussed.